Nutrition of Tissue-Cultured Plants of Dendrobium Sonia-17 - Uma Maheswari R (Department of Horticulture, College of Agriculture, 1999)
The present study was undertaken to evolve the nutrient dosage combination which will produce maximum vegetative growth of tissue-cultured and ex vitro established Dendrobium Sonia - 17 plants. The experiment was conducted from October 1997 to June 1998. The varying nutrient dosages selected were 2.0, 6.0 and 10.0 mg of N, P and K at different combinations.